It’s geopolitics, stupid: explaining Russia’s Ukraine policy - Elias Götz (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
What lies behind Russia’s annexation of Crimea and its confrontational policies towards Ukraine? This article challenges the widely held perspective that President Putin’s personality and his security-service background is the central driver of Russia’s Ukraine policy. Instead, it puts forward a geopolitical explanation that emphasizes three factors: Ukraine’s geographic location; the EU’s increased activism in Eastern Europe; and the pro- western orientation of the new government in Kiev. Together, these three factors provide Russia with a strong incentive to pursue an assertive policy towards Ukraine. Moscow’s main aim is to regain some control over Kiev’s foreign policy orientation and, if that is not possible, to establish a belt of pro-Russian provinces in Ukraine’s east. The findings of this article suggest, moreover, that the West ’s current policies towards Russia are ineffective and potentially counterproductive. A major readjustment is urgently needed.